BTS/NICE/SIGN guideline for asthma 2024: Diagnosis, monitoring and chronic asthma management. How does this compare to GINA 2024? - Kevin Gruffydd-Jones (npj Primary Care Respiratory Medicine)
The British BTS/NICE/SIGN Asthma Guideline was launched in November 2024 and represents a major shift in asthma diagnosis and management in the United Kingdom. The British Guideline places emphasis on markers of eosinophilic inflammation as initial key diagnostic tests whereas GINA places emphasis on test of reversible airflow limitation. Both documents acknowledge that there is no one “gold-standard” test and, especially in areas of the world where the is limited or delayed access to tests, the IPCRG “jigsaw puzzle” approach to asthma diagnosis may he particularly useful. The BTS/NICE/SIGN guideline provides strong economic evidence to support the GINA strategy approach of single anti-inflammatory-reliever (AIR) and Maintenance and Reliever (MART) therapies as the cornerstone of asthma management in people age 12 and over.